Development of financial support of innovative activity in the Republic of Kazakhstan - Orynbassarova, Y.; Legostayeva А.; Omarova А.; Ospanov, G.; Grelo, M.F. (BUKETOV BUSINESS REVIEW, 2017)
In article are considered the еhe modern economic strategy of RK is directed to creation of the balanced and flexible economy capable to compete at the international level, to provide acceleration of economic growth and increase in welfare of the population. Kazakhstan supports a course of innovative development as innovations in present conditions determine the level of economic growth. In this regard the role of innovative policy of the country increases. In realization of innovative policy of the state and creation of powerful industrial basis of the state, it is possible to note that sufficient financing of all industrial projects has to become fundamentals of innovative policy of the Republic of Kazakhstan, and for this purpose it is necessary to construct and realize investment policy competently. Today in the Republic of Kazakhstan it is created and successfully all necessary base for creation of innovative economy assuming creation of full-fledged innovative system in which several components - innovative and scientific infrastructure, including science and technology parks, design offices functions. It is financial infrastructure, first of all, innovative grants, venture funds, project financing and, of course, active participation of business.